F FACTORS AFFECTING EMPLOYMENT MOTIVATION AND PERFORMANCE OF EMPLOYEES IN THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION - Raka, Agung Raka (Advances in Social Sciences Research Journal, 2021)
Public service employee are required to provide good performance to people who need population administration services. This study aimed to analyze the factors that influence work motivation and official employee performance. This study used a sample of 108 state civil servants through the purposive sampling technique at the Department of Population and Civil Registration. The exogenous variables in this study are incentives and workload, while the endogenous variables are work motivation and employee performance. The measurement of the variables was carried out using a Likert scale. Path Analysis did data analysis with a multiple linear regression approach. The study results indicate a direct and positive, and significant effect between the incentive variables and employee work motivation, workload and employee work motivation, incentives and employee performance, workload and employee performance, and work motivation and employee performance. This effect can be shown by the coefficient values of 0.154, 0.132, 0.145, 0.126, and 0.529. The results of this study support that the incentive factors and workload are given to employees can improve the performance of the Population and Civil Registration Service employees. Clarity and openness to sources of motivation need to be done to support employee performance. Research provides recommendations on the importance of attention to improve employee professionalism so that employees will be able to perform well.